IMPLEMENTASI ALGORITMA KOLONI SEMUT PADA TRAVELING SALESMAN PROBLEM MENGGUNAKAN MATLAB 7.8 - Wenefrida Tulit Ina; Molina O. Odja (Universitas Nusa Cendana, 2022)
Ant algorithm is a methodology, that is generated through the observation of theants. In Ant algorithm, ants serveas an agent assigned to find a solution to a problem the shortest route. Ant algorithm has been applied in many fields, one of which is to see a solution in the search for the shortest routeto theTraveling Salesman Problem (TSP). Research conducted Ant algorithm is to make an application to the determination of the shortest distanceas the coding matlab program in the selection of the shortest route in order to help determine the shortest distance from a trajectory. The test results showed Shortest Route Program applications using ant algorithm with alarge value of Alpha=1.0; Beta=1.0; Rho=0.5andT-Beginning =0:01with city coordinates[10 0; 300; 15,20; 25,20; 1030; 30,30] withthe number of iterations or 10cycles to obtain the path length of the shortest path length=1-3-5-6-4-2so that the shortest path is: 103.5917cm. Effects of changes in the variation of the experiment Rho. Rho smallest value obtained for a total of 10 cycles or iterations with the shortes tpath length is103.5917. At Rho: 12:50 with a large average value of 3 times the trial time calculation is: 3.815sec.